Effect of coagulation agents on morphology and structure of cellulose/silk fibroin films with 1-butyl-3-ethylimidazolium chloride as solvent. (July 2014) - Mukuze, K. S.; Yao, Y.; Xia, X.; Zhang, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Cellulose/silk blend solutions were prepared in 1-butyl-3-methylimidazolium chloride [BMIM]Cl and films were subsequently formed from coagulation baths. Fourier Transform Infrared (FTIR) spectroscopy, wide-angle X-ray diffraction (WAXD) and scanning electron microscope (SEM) were carried out to compare the influence of coagulation agents on the weight content of silk fibroin (wSF), secondary structure and morphology of cellulose/silk blend films. Rough and scaly films were formed due to rapid crystallisation induced by ethanol. When films were coagulated in acetonitrile, a change from random coil to β-sheet structure of silk fibroin and from cellulose I to cellulose II of cellulose occurred favourably. When blend films were coagulated in water, there was a protein component extraction which diffused into the coagulation bath.